The handbook of global agricultural markets : the business and finance of land, water, and soft commodities - Nijs, Luc (Pal grave Macmillan, 2014)
"The Handbook of Global Agricultural Markets is a one-stop reference for practitioners and academics in finance, business, and economics, providing a holistic reference to the international agriculture business. The book takes a multidisciplinary approach to the topic, looking at the issues, opportunities, and investible themes in the global agricultural space, combining both research and practical tools for analyzing topics and assessing risks. A central theme of the book is the role of the agriculture industry as an emerging market, how the industry has developed and grown to date, and prospects for the future. Readers will gain an understanding of the industry from the perspectives of producers, consumers, and catalysts. The book provides coverage of the following key commodity industries: wheat, soybean, corn, coffee, cotton, rice, ethanol, oats, lumber, cacao, orange juice, soy oil, live cattle, live hogs and feed cattle, water. This book will appeal to a range of readers, from the institutional investor who wants to invest in commodities; businesses, angels, and private equity houses who want to invest in agriculture projects; businesses looking for market entry; and academics who are researching the global agriculture industry. "--